ІМПУЛЬСНІ ЕЛЕКТРОДИНАМІЧНІ СИЛИ В БАГАТОВИТКОВОМУ ТОРЦЕВОМУ ЦИЛІНДРИЧНОМУ ІНДУКТОРІ - Ращепкiн, А.П. (Інститут електродинаміки Національної академії наук України, 2018)
In the processes of electroplastic and magnetoplastic deformations of metals, the method of weakening the impulse electrodynamics forces of interaction between a metal being processed and a multi-turn end cylindrical inductor is substantiated by using an electrically conductive metal screen. Complete elimination of electrodynamics forces is achieved by adjusting the gap between the inductor and the shield. Unipolar current pulses in the inductor are excited by discharging the electrical capacitance to the inductor using a controlled thermistor. Electromagnetic processes in such an electrodynamics system are examined using known methods developed in theoretical electrical engineering for analyzing the discharge processes of capacitance for active-inductive loading, as well as numerical methods for finite element calculations. References 7, figures 6.